Irisin is more strongly associated with leisure-time physical activity than resistin and high-density lipoprotein cholesterol are - María del Cristo Rodríguez-Pérez; Titta Katariina Kontro; Delia Almeida González; Beatriz Gómez Álvarez; Itahisa Marcelino Rodríguez; y Antonio Cabrera de León (Journal of Exercise Science & Fitness, 2022)
Background/Objectives: Irisin is a myokine with a potential role in cardiometabolic diseases, but previous studies have described inconsistencies between serum irisin and physical activity (PA). Our aim was to analyze the relationship between serum irisin and leisure-time PA (LTPA) in a large sample of the general adult population, and secondarily, to evaluate its relationship with two PA-related biomarkers (HDL cholesterol and resistin). Methods: A cross-sectional study was nested in the “CDC of the Canary Islands” cohort participants (n = 3827, 18–75 years, 60% women). PA was collected by administering the Minnesota leisure-time physical activity questionnaire, and physical examination and blood tests (irisin, resistin, HDL-cholesterol) were performed. Results: Irisin inversely correlated with BMI (p < 0.001 in women) and resistin (p = 0.038 in women, p = 0.004 in men), and directly with HDL cholesterol (p < 0.001in women). There was a direct association of irisin with leisure-time and energy expenditure in light, moderate and vigorous LTPA, which was stronger in women than men. The distribution of leisure-time and PA variables across irisin quintiles showed a significant trend, except for light LPTA in men. Adjusting for age, sex and BMI, the association of irisin with leisure-time and LTPA variables was stronger than the association of these variables with resistin and HDL cholesterol, reaching the strongest association for irisin with the 80th percentile of time of LTPA (OR = 2.57; 95% CI = 2.00–3.31). Conclusions: There is a direct and independent association between serum irisin levels and LTPA in the general adult population, which is stronger than other biomarkers of PA. Findings on exercise-related irisin support the possibility of irisin health benefits.